Penerapan Komunikasi Efektif Isobar Dengan SBAR Pada Pengetahuan Dan Kualitas Operan Perawat Di Rumah Sakit - Nellyta; Hadi, Muhammad; Sulaeman, SUhendar (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Ineffective communication is one of the factors that can endanger patient safety. One of the effectivecommunication methods in nursing is operant. This study identified the effect of effective communicationtraining with the ISOBAR and SBAR methods on the knowledge and quality of nurse handover. This researchwith a quasi-experimental design involved 20 nurses who were divided into two groups, namely ISOBAR andSBAR. Questionnaires and observation forms in data collection, and analysis of General Linear Model Repeat Measures (GLM-RM) to measure the effect of effective communication training on operant knowledgeand quality. Effective communication training with the ISOBAR and SBAR methods was effective inincreasing the knowledge of nurses and the quality of the handover (p <0.05). The mean knowledge scoreincreased from 50.76 to 84.61 for the ISOBAR group and 56.16 to 83.85 for the SBAR group. The mean scoreof operand quality also increased from 69.63 to 95.20 in the ISOBAR group and 73 to 92 in the SBAR group.The overall score of knowledge and operant quality in the ISOBAR group was higher than the SBAR group.